The Knowledge-Enabled Organization: Moving from "Training" to "Learning" to Meet Business Goals - Daniel R. Tobin (New York AMACOM, 1998)
If the knowledge and skills of employees are a company's biggest competitive asset, why are so many organizations riddled with unproductive, irrelevant training departments and activities? Because they're being ripped off in a $50 billion "Great American Training Robbery," says Daniel Tobin in this strong, frank -- and ultimately rejuvenating -- critique of the current state of employee learning. And it's time for senior managers and human resources professionals to enact change. Tobin outlines a new approach to learning, one that links "training and development" with viable, job-related, bottom-line driven activities. His model operates on individual, work unit, and corporate levels, with each area continually sharing information and skills -- to create a dynamic, actively learning, knowledge-enabled organization. Filled with instructive real-world examples, The Knowledge-Enabled Organization supplies a comprehensive and practical game plan for implementing this kind of strategic, results-driven training. It explains how ** transform the way that training departments think and act ** ensure that every training dollar spent contributes to corporate financial goals -- and individual career goals ** expand and diversify an employee's learning activities ** create a knowledge network to support learning ** build and maintain a positive learning environment.
Age Group: Adult
Includes bibliographical references and indexes.
Keywords: Training of employees; Employer-supported education